From Mice to Mole-Rats: Species-Specific Modulation of Adult Hippocampal Neurogenesis - Oosthuizen, Maria K. (Frontiers in Neuroscience, 2017)
Rodent populations living in their natural environments have very diverse ecological and life history profiles that may differ substantially from that of conventional laboratory rodents. Free-living rodents show species-specific neurogenesis that are dependent on their unique biology and ecology. This perspective aims to illustrate the benefit of studying wild rodent species in conjunction with laboratory rodents. African mole-rats are discussed in terms of habitat complexity, social structures, and longevity. African mole-rats are a group of subterranean rodents, endemic to Africa, that show major differences in both intrinsic and extrinsic traits compared to the classical rodent models. Mole-rats exhibit a spectrum of sociality within a single family, ranging from solitary to eusocial. This continuum of sociality provides a platform for comparative testing of hypotheses. Indeed, species differences are apparent both in learning ability and hippocampal neurogenesis. In addition, social mole-rat species display a reproductive division of labour that also results in differential hippocampal neurogenesis, independent of age, offering further scope for comparison. In conclusion, it is evident that neurogenesis studies on conventional laboratory rodents are not necessarily representative, specifically because of a lack of diversity in life histories, uniform habitats and low genetic variability. The observed level of adult neurogenesis in the dentate gyrus is the result of an intricate balance between many contributing factors, which appear to be specific to distinct groups of animals. The ultimate understanding of the functional and adaptive role of adult neurogenesis will involve research on both laboratory animals and natural rodent populations.